A study on socio-demographic and environmental factors association with viral diarrhea in under 5 year children - Verma, Pratima; Rawat, Sumit K.; Uppal, Rashmi; Gupta, Mansi; Agarwal, Ruchi (International Journal Of Community Medicine And Public Health, 2025)
Background: The data associated with diarrheal diseases are limited in low and middle-income countries where it possesses a great threat to the population and its economy. Risk factors that can make a population more vulnerable to diarrhea can be environmental or behavioral, yet differ among individuals, populations, countries, and geographies. Finding out the etiology, socio-demographic determinants and environmental factors occurrence might help in designing intervention strategies. Methods: A cross-sectional study was conducted for one year from July 2021 to July 2022 in Department of Microbiology. Stool samples of 150 under 5 year children were included and tested with multiplex PCR and monoplex PCR to detect viruses causing diarrhea. Data was analyzed and p value <0.05 considered as statistically significant. Results: Out of 150 total samples 18.7% (28/150) were positive for viruses causing diarrhea. Rotavirus was most common cause for diarrhea. Maximum cases found in infants 53.6% followed by toddler 25%, and early childhood 21.4%. Out of 28 positive cases, 64.3% were males and 35.7% females. The maximum cases seen from July-September 50% and in rural areas 31% compared to urban areas 9%. Conclusions: A number of socio-demographic determinants such as rural-urban residence along with child’s age are associated with occurrence of diarrhea in under 5 children. Concerning environmental factors such as seasonal variations in specific geographic regions are associated with diarrheal disease with higher prevalence of viral diarrhea occurring in rainy season in current study.